Pouchitis after ileal pouch-anal anastomosis for ulcerative colitis occurs with increased frequency in patients with associated primary sclerosing cholangitis. (February 1996) - Penna, C; Dozois, R; Tremaine, W; Sandborn, W; LaRusso, N; Schleck, C; Ilstrup, D
Abstract : Primary sclerosing cholangitis (PSC), present in 5% of patients with ulcerative colitis, may be associated with pouchitis after ileal pouch-anal anastomosis. The cumulative frequency of pouchitis in patients with and without PSC who underwent ileal pouch-anal anastomosis for ulcerative colitis was determined. A total of 1097 patients who had an ileal pouch-anal anastomosis for ulcerative colitis, 54 with associated PSC, were studied. Pouchitis was defined by clinical criteria in all patients and by clinical, endoscopic, and histological criteria in 83% of PSC patients and 85% of their matched controls. PSC was defined by clinical, radiological, and pathological findings. One or more episodes of pouchitis occurred in 32% of patients without PSC and 63% of patients with PSC. The cumulative risk of pouchitis at one, two, five, and 10 years after ileal pouch-anal anastomosis was 15.5%, 22.5%, 36%, and 45.5% for the patients without PSC and 22%, 43%, 61%, and 79% for the patients with PSC. In the PSC group, the risk of pouchitis was not related to the severity of liver disease. In conclusion, the strong correlation between PSC and pouchitis suggest a common link in their pathogenesis.